2015
DOI: 10.1589/jpts.27.1933
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dynamic exercise utilizing PNF patterns on abdominal muscle thickness in healthy adults

Abstract: [Purpose] The purpose of this study is to examine the effects of dynamic exercise utilizing the PNF (proprioceptor neuromuscular facilitation) patterns accompanied by abdominal drawing-in exercises on abdominal muscle thickness in healthy adults. [Subjects] The total number of subjects was 30;15 were randomly placed in the training group (TG), and the remaining 15 made up the control group (CG). [Methods] The subjects in the TG conducted 3–5 sets of dynamic exercises utilizing the PNF patterns each day, 3 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Cayco et al found that proprioceptive neuromuscular facilitation was effective in enhancing balance, strength, and mobility in an older adult with chronic stroke 8) . Gong examined the PNF pattern exercise and found that when the exercise was applied to normal adults for six weeks, the thickness of the external obliquus abdominis, internal obliquus abdominis, and transversus abdominis muscles increased 7) . Cho and Gong showed that the application of PNF pattern exercise to normal adults for six weeks improved trunk inclination, pelvic position, pelvic torsion, pelvic rotation, and the position of their scapular 10) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cayco et al found that proprioceptive neuromuscular facilitation was effective in enhancing balance, strength, and mobility in an older adult with chronic stroke 8) . Gong examined the PNF pattern exercise and found that when the exercise was applied to normal adults for six weeks, the thickness of the external obliquus abdominis, internal obliquus abdominis, and transversus abdominis muscles increased 7) . Cho and Gong showed that the application of PNF pattern exercise to normal adults for six weeks improved trunk inclination, pelvic position, pelvic torsion, pelvic rotation, and the position of their scapular 10) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on balance, such the effect of core stability, dual tasking, and sensory strategies programs on balance 6) ; the effect of backward walking training on balance performance 3) ; the effect of PNF on the balance of older adults with chronic stroke 8) ; and the effect of aquatic exercise on balance 9) . Moreover, studies have analyzed the effect of PNF pattern exercise on the changes in the thickness of the abdominis 7) and on postural changes 10) . However, no study has yet analyzed the effects of dynamic exercise utilizing the PNF patterns on the balance of healthy adult participants.…”
Section: The Journal Of Physical Therapy Science the Journal Of Physimentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the modified wall squat exercise has been reported to increase TrA and IO thickness 13 ) . Moreover, dynamic exercises utilizing PNF patterns has been reported to be effective at improving deep abdominal muscle thickness 14 ) , and the isometric hip abduction squat was reported to be more effective at improving TrA and IO thickness than the standard and isometric hip abduction squat exercises 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted on different exercises and the use of deep abdominal muscles that are important for lumbar stability, including the effect of the prone bridge and supine bridge exercises on deep abdominal muscle thickness 12 ) , the effect of the modified wall squat exercise on deep abdominal muscle thickness 13 ) , the effect of dynamic exercises utilizing PNF patterns on deep abdominal muscle thickness 14 ) , the effect of conducting the bridge exercise on an unstable surface on deep abdominal muscle thickness 15 ) , and the effect of isometric hip abduction squats on deep abdominal muscle thickness 16 ) . However, exercises conducted in a standing posture are not appropriate for patients with problems of the lower limbs or lumbar pain.…”
Section: Introductionmentioning
confidence: 99%